2010
DOI: 10.1042/bst0381110
|View full text |Cite
|
Sign up to set email alerts
|

The function of the NineTeen Complex (NTC) in regulating spliceosome conformations and fidelity during pre-mRNA splicing

Abstract: The NineTeen Complex (NTC) of proteins associates with the spliceosome during pre-mRNA splicing and is essential for both steps of intron removal. The NTC and other NTC-associated proteins are recruited to the spliceosome where they participate in regulating the formation and progression of essential spliceosome conformations required for the two steps of splicing. It is now clear that the NTC is an integral component of active spliceosomes from yeast to humans and provides essential support for the spliceosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 50 publications
4
105
0
5
Order By: Relevance
“…These included MODIFIER OF SNC1 4 (MOS4) that shows homology to human Breast Cancer-Amplified Sequence 2, the Arabidopsis CELL DIVISION CYCLE5 (CDC5) Myb-transcription factor, and the WD-40 repeat PLEIOTROPIC REGULATORY LOCUS1 (Palma et al, 2007). Notably, their counterparts in humans and yeast interact with one another and with Prp19 (for Precursor RNA Processing 19) in the core of the Nineteen Complex (so named for Prp19) that is essential for catalytic activation of the spliceosome (Hogg et al, 2010). A proteomics approach for proteins interacting with MOS4 subsequently identified two closely related proteins with sequence homology to Prp19, termed MAC3A (for MOS4-associated complex 3A) and MAC3B (Monaghan et al, 2009).…”
Section: Factors Involved In As Of R Genes and Plant Defensementioning
confidence: 99%
“…These included MODIFIER OF SNC1 4 (MOS4) that shows homology to human Breast Cancer-Amplified Sequence 2, the Arabidopsis CELL DIVISION CYCLE5 (CDC5) Myb-transcription factor, and the WD-40 repeat PLEIOTROPIC REGULATORY LOCUS1 (Palma et al, 2007). Notably, their counterparts in humans and yeast interact with one another and with Prp19 (for Precursor RNA Processing 19) in the core of the Nineteen Complex (so named for Prp19) that is essential for catalytic activation of the spliceosome (Hogg et al, 2010). A proteomics approach for proteins interacting with MOS4 subsequently identified two closely related proteins with sequence homology to Prp19, termed MAC3A (for MOS4-associated complex 3A) and MAC3B (Monaghan et al, 2009).…”
Section: Factors Involved In As Of R Genes and Plant Defensementioning
confidence: 99%
“…18 Formation of the next intermediate in spliceosome assembly, the A complex, requires ATP hydrolysis and results in the stable recruitment of additional factors to the pre-mRNA, most notably the U2 snRNP. Proteomic analysis has shown that the Prp19 complex (PRP19C), which plays an important role in spliceosome activation, 19 is also associated with the spliceosome in A complex. 16 Following A complex formation, the U4/U6 and U5 snRNPs become associated with the spliceosome as part of a preassembled unit known as the tri-snRNP, forming the B complex.…”
Section: Ctd Structure and Modificationmentioning
confidence: 99%
“…In this context, the recent demonstration of a direct interaction between Cwc24 and Cef1 is of interest (Goldfeder and Oliveira 2008). Cef1 is a core protein of the NTC complex, which acts as a major assembly platform, integrating and coordinating many molecular interactions in B act and B* complexes (Tsai et al 1999;Hogg et al 2010). An alternative primary target of Prp2 could be one of the U2 SF3a/b proteins, which are known to interact with the premRNA near the BS.…”
Section: Cwc24 Functions In the Generation Of An Active Spliceosome Bmentioning
confidence: 99%